USING BLOCK DIAGRAMS WHEN STUDYING HIGHER MATHEMATICS - Zakusilo , Anatolij (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2023)
Arguments are presented in favor of computer support for mathematical training of male and female students in distance learning conditions. The expediency of using structural schemes in the process of systematizing the teaching of individual sections of higher mathematics is substantiated.